Review of the Polistes (Polistella) "Stenopolistes" species-group (Hymenoptera: Vespidae: Polistinae) from Vietnam, with description of a new species and key to species - Nguyen, Lien T.p.; Carpenter, James M. (Zootaxa, 2016)
The "Stenopolistes" species-group of the subgenus Polistella Ashmead, 1904 comprising in Vietnam by six species. Polistes adsimilis Nguyen & Carpenter sp. nov. is described and figured. Polistes khasianus Cameron, 1900 is confirmed to occur in Vietnam, P. pallidus Gusenleitner, 2011 is newly recorded from Vietnam. A key to Vietnamese species is provided. The nest of P. khasianus is described.